2013
DOI: 10.1002/esp.3493
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial laser scanning of rock slope instabilities

Abstract: This manuscript presents a review on the application of a remote sensing technique (terrestrial laser scanning, TLS) to a well-known topic (rock slope characterization and monitoring). Although the number of publications on the use of TLS in rock slope studies has rapidly increased in the last 5-10 years, little effort has been made to review the key developments, establish a code of best practice and unify future research approaches. The acquisition of dense 3D terrain information with high accuracy, high dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(190 citation statements)
references
References 174 publications
(307 reference statements)
2
176
0
1
Order By: Relevance
“…The creation of a representative inventory is also a function of the smallest event size that can be detected and the temporal frequency of monitoring compared to the rate at which such small events occur. Abellán et al (2014) suggested that the spatial resolution of rockfall monitoring should be sufficient to discretise the smallest events in a magnitude-frequency distribution and that the recording frequency should fall below the timescale on which superimposition and coalescence may occur. In practice, defining this timescale a priori is challenging and requires the ability to monitor the rock face over a sustained period in (near) real time.…”
Section: Temporal Resolution Of Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The creation of a representative inventory is also a function of the smallest event size that can be detected and the temporal frequency of monitoring compared to the rate at which such small events occur. Abellán et al (2014) suggested that the spatial resolution of rockfall monitoring should be sufficient to discretise the smallest events in a magnitude-frequency distribution and that the recording frequency should fall below the timescale on which superimposition and coalescence may occur. In practice, defining this timescale a priori is challenging and requires the ability to monitor the rock face over a sustained period in (near) real time.…”
Section: Temporal Resolution Of Monitoringmentioning
confidence: 99%
“…In this section we describe the protocol for scan alignment applied to the nearcontinuous dataset. As discussed by Abellán et al (2014), aligning point clouds can be undertaken using common surveyed and modelled targets combined with measured global coordinates (Teza et al, 2007;Olsen et al, 2009), featurebased registration based on the planarity and curvature of surfaces (e.g. Besl and Jain, 1988;Belton and Lichti, 2006;Rabbani et al, 2006), and point-to-point and point-to-surface methods, which use iterative closest point (ICP) alignment to progressively reduce the distance between two clouds (Besl and McKay, 1992;Chen and Medioni, 1992;Zhang, 1994).…”
Section: Precise Alignmentmentioning
confidence: 99%
“…in order to enable fast advancement in the application of the sensor in disciplines such 48 as rock mechanics, geotechnics and earth sciences, development of new algorithms is 49 needed (Abellán et al, 2014). 50…”
Section: Introductionmentioning
confidence: 99%
“…Architecture reconstruction (Santagati et al, 2013), heritage documentation and preservation (Fanti et al, 2013); 3. Environmental monitoring and disaster prevention (Abellán et al, 2014). Since the objects to be scanned are either large (e.g., a very tall building) or occluded/self-occluded (e.g., a complex industrial site), a scanning network consisting of multiple scan locations is usually required to provide complete coverage of the object, which is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%